Exploration of potential yeast (Candida maltosa) from mozzarella cheese and its prospect for probiotic activity - Raiyaan, Kazi Ruksaad (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.